2014
DOI: 10.1016/j.humov.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The coupling between gaze behavior and opponent kinematics during anticipation of badminton shots

Abstract: a b s t r a c tPurpose: We examined links between the kinematics of an opponent's actions and the visual search behaviors of badminton players responding to those actions. Method: A kinematic analysis of international standard badminton players (n = 4) was undertaken as they completed a range of serves. Video of these players serving was used to create a life-size temporal occlusion test to measure anticipation responses. Expert (n = 8) and novice (n = 8) badminton players anticipated serve location while wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 20 publications
(33 reference statements)
6
36
1
1
Order By: Relevance
“…execution phase of 1,900 ms duration, see Alder et al, 2014). Therefore, the duration of the 548 task may not have provided sufficient time for the differences in fixation frequency normally 549 found for anxiety and for fixation duration differences to become apparent.…”
Section: < 02) 417mentioning
confidence: 99%
See 3 more Smart Citations
“…execution phase of 1,900 ms duration, see Alder et al, 2014). Therefore, the duration of the 548 task may not have provided sufficient time for the differences in fixation frequency normally 549 found for anxiety and for fixation duration differences to become apparent.…”
Section: < 02) 417mentioning
confidence: 99%
“…The video-based task was the same video-based temporal occlusion 220 test as used in Alder et al (2014). During the task, the badminton players were required toanticipate serves from video of a doubles match filmed from the first person perspective that 222 were shown as a series of clips on a large screen and occluded around shuttle/racket contact.…”
Section: Tasks 219mentioning
confidence: 99%
See 2 more Smart Citations
“…Williams and colleagues (2002) found that talented tennis players were better at anticipating the forehand and backhand direction from the movement of the body and hip area of the competitor compared to less skilled tennis players. It is observed that the effects of gender, age, and sports history on the time of anticipation are investigated in other studies conducted with the anticipation time (Xu et al, 2016;Ting et al, 2017;Alder et al, 2014).…”
Section: Discussionmentioning
confidence: 99%